Physical Activity and Stress in employees of a public university in Bahia during the COVID-19 pandemic - Santos , Edson Leão dos; Azevêdo , Denize Pereira de; Ferreira, Ana Vitória Lima; Assunção, Tâmara Verdino Morais; Barros, João Henrique Cerqueira (Seven Editora, 2023)
The research aimed to analyze the association between the practice of Physical Activity (PA) and the prevalence of stress in technical-administrative employees of UEFS during the COVID-19 pandemic context. This is a cross-sectional epidemiological study, conducted online, in which the instruments for data collection were the sociodemographic questionnaire, the International Physical Activity Questionnaire (IPAQ) long version and the Inventory of Stress Symptoms for Adults (ISSL). The statistical data showed that, among the 143 employees who collaborated with the research, 55.9% presented stress; among them, 53.8% were in the resistance phase. In addition, the data also showed that 60.0% had a high level of PA. Moreover, the data showed that there was no statistically significant association (p<0.05) between the practice of PA and the prevalence of stress (p-value = 0.635) and its phases (p-value = 0.183). Therefore, we need to think about people in an integral way and reflect on the various spheres in which they find themselves in society. In addition, the university needs to think about strategies of assistance and support to the servers, since they were in a psychic suffering during the context of the pandemic and with the return in person the demands became excessive. The purpose of the research was to contribute and think of strategies and improvements that contribute to the general health of these workers. DOI:https://doi.org/10.56238/emerrelcovid19-031